1996
DOI: 10.1097/00006123-199606000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Treatment of Malignant Gliomas with Intramuscularly Administered Polyinosinic-Polycytidylic Acid Stabilized with Polylysine and Carboxymethylcellulose: An Open Pilot Study

Abstract: Polyinosinic-polycytidylic acid stabilized with polylysine and carboxymethylcellulose (poly-ICLC) (10-50 mcg/kg, administered intramuscularly one to three times weekly) was given for < or = 56 months to 38 patients with malignant gliomas. There was minimal or no toxicity. Twenty of 30 patients (66%) receiving at least twice weekly poly-ICLC showed regression or stabilization of gadolinium-enhancing tumor, as revealed by magnetic resonance imaging (median = 65% volume decrease). All but one patient with anaplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Fatigue, myalgia and pain at the injection site were the main adverse events; these events were not substantially different from the toxicities witnessed in the previous trial which utilized poly-ICLC in high-grade glioma patients. No patients went off-study because of toxicity [26]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatigue, myalgia and pain at the injection site were the main adverse events; these events were not substantially different from the toxicities witnessed in the previous trial which utilized poly-ICLC in high-grade glioma patients. No patients went off-study because of toxicity [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Twenty of 38 patients also received concurrent CCNU at 120mg/m2 once every six weeks while others received no chemotherapy. This study showed up to a 40-fold increase in serum OAS product and toxicity was mild [26]. 66% of patients (including all 11 newly diagnosed AA) receiving at least twice-weekly poly-ICLC showed regression or stabilization of gadolinium enhancing tumor volume on MRI for at least 6 months from study entry.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In multiple previous reports it was shown that poly-ICLC induced greater activation of natural killer cells at 10 mcg/kg as compared with higher doses, and the most active biological dose of 20 mcg/kg was established in adult trials. 14,21 The FDA agreed with this plan to do a low-dose study without a phase I dose escalation.…”
Section: Methodsmentioning
confidence: 99%
“…The safety and tolerability of long-term, low-dose intramuscularly administered poly-ICLC in the dose range of 20 mcg/kg 2 to 3 times weekly, in adult patients with malignant gliomas was established. Prolonged, quality survival with tumor stabilization or regression confirmed by magnetic resonance imaging for most patients with anaplastic astrocytomas and glioblastomas prompted Salazar et al 14 to conclude that more extensive laboratory and controlled clinical studies with poly-ICLC are warranted. Other adult trials with recurrent and newly diagnosed glioblastoma found that poly-ICLC was well tolerated as a single agent and in combination, but did not improve progression-free survival.…”
mentioning
confidence: 99%